Small-molecule drugs for cystic fibrosis: Where are we now?. (February 2022) - Laselva, Onofrio; Guerra, Lorenzo; Castellani, Stefano; Favia, Maria; Di Gioia, Sante; Conese, Massimo
Abstract: The cystic fibrosis (CF) lung disease is due to the lack/dysfunction of the CF Transmembrane Conductance Regulator (CFTR), a chloride channel expressed by epithelial cells as the main regulator of ion and fluid homeostasis. More than 2000 genetic variation in the CFTR gene are known, among which those with identified pathomechanism have been divided into six mutation classes. A major advancement in the pharmacotherapy of CF has been the development of small-molecule drugs hitting the root of the disease, i.e. the altered ion and fluid transport through the airway epithelium. These drugs, called CFTR modulators, have been advanced to the clinics to treat nearly 90% of CF patients, including the CFTR potentiator ivacaftor, approved for residual function mutations (Classes III and IV), and combinations of correctors (lumacaftor, tezacaftor, elexacaftor) and ivacaftor for patients bearing at least one the F508del mutation, the most frequent mutation belonging to class II. To cover the 10% of CF patients without etiological therapies, other novel small-molecule CFTR modulators are in evaluation of their effectiveness in all the CFTR mutation classes: read-through agents for Class I, correctors, potentiators and amplifiers from different companies for Class II-V, stabilizers for Class VI. In alternative, other solute carriers, such as SLC26A9 and SLC6A14, are the focus of intensive investigation. Finally, other molecular targets are being evaluated for patients with no approved CFTR modulator therapy or as means of enhancing CFTR modulatory therapy, including small molecules forming ion channels, inhibitors of the ENaC sodium channel and potentiators of the calcium-activated chloride channel TMEM16A. This paper aims to give an up-to-date overview of old and novel CFTR modulators as well as of novel strategies based on small-molecule drugs. Further investigations in in-vivo and cell-based models as well as carrying out large prospective studies will be required to determine if novel CFTR modulators, stabilizers, amplifiers, and the ENaC inhibitors or TMEM16A potentiators will further improve the clinical outcomes in CF management. Highlights: Cystic fibrosis (CF) is due to mutations in the CFTR gene, encoding an epithelial chloride/bicarbonate channel. CFTR mutations lead to alterations in airway ion and fluid homeostasis and airway surface liquid (ASL) hyper-viscosity. Other channels and transporters are involved in CF-associated lung disease, including ENaC, TMEM16A, SLC6A14 and SLC26A9. Small-molecule CFTR modulators, such as the triple combination Trikafta™, can treat around 90% of CF individuals. The development of novel modulators, that could treat patients bearing non-responsive CFTR mutations, is currently pursued. ENaC inhibitors are considered an interesting approach to decrease ASL dehydration and are in phase 2 clinical trials. Activators or potentiators of TMEM16A, a chloride/bicarbonate channel alternative to CFTR, are in the pre-clinical phase. Amphotericin B, shown to ameliorate ASL properties, could be an option for mutation-agnostic therapeutic approaches. Small-molecule drugs targeting other channels modifier of CFTR, such as SLC6A14 and SLC26A9, should be further investigated.